PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS PEMBERIAN REWARD TERHADAP HASIL BELAJAR MATEMATIS DI KELAS IV SD NEGERI 060919 MEDAN - Rizka Pahmawati Regina Br Sitanggang; Ribka Kariani Sembiring; Juliana; Darinda Sofia Tanjung; Rumiris Lumban Gaol; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of the Reward-based Problem Based Learning learning model on the mathematical learning outcomes of class IV at SD Negeri 060919 Medan Sunggal for the 2024/2025 academic year. The procedures and techniques used in research are called research methodology. The aim of this quantitative research strategy is to identify factors that contribute to the success or failure of various learning approaches in improving academic achievement in mathematics classes with fractions as the main material in class IV. This can be seen from the average student pretest score of 43.33 and the average score of -student posttest average 74.33. Based on the results of the hypothesis test (t-test) with a value of ≥, namely 5,806 2.048 at a significance level of 0.000 0.05. These data can show that Ha is accepted, namely that there is an influence between the Problem Based Learning learning model based on giving rewards (X) on student learning outcomes (Y). At the end of the lesson, the researcher provided treatment using a Problem Based Learning learning model based on giving rewards when teaching, then the researcher tested the students again by giving a posttest of 10 questions to see the value of the treatment given. By using the Problem Based Learning learning model based on giving rewards, students' posttest learning outcomes increased with an average score of 74.33 and there were 29 students who completed and 1 student who did not complete. So the final step that the researcher took was to give a 25-item Problem Based Learning model questionnaire to students.